Effectiveness of diffuse ultrasound for evaluation of micro-cracking damage in concrete. (October 2019) - Ahn, Eunjong; Shin, Myoungsu; Popovics, John S.; Weaver, Richard L.
Abstract: The main objective of this research is to investigate the applicability of diffuse ultrasound to the evaluation of distributed micro-cracking damage in concrete. To simulate the micro-cracking damage, polypropylene fibers with very low mechanical characteristics were embedded in concrete specimens, using three different fiber amounts (0, 0.3, and 0.6% by volume) to represent three different damage levels. Ultrasonic diffusivity and dissipation coefficients within a frequency range of 200 to 450 kHz, which represents the multiple scattering regime for typical concrete, are used to characterize the micro-cracking conditions of the specimens. Additionally, effects of the spacing between the source and receiver on the diffusion of ultrasound are explored. The test results confirm that the diffusivity decreases approximately 25% and dissipation increases 32% with increasing damage level, and they are fairly independent of the transducer spacing, which suggests promise for practical application of the method for concrete inspection in the field.